Forum on Drug Discovery, Development, and Translation: 2010 Annual Report - Institute of Medicine (The National Academies Press, 2011)
In 2010, the scientific and business landscape of drug development was fraught with continued uncertainty and risk. New paradigms for discovering and developing drugs were sought to bridge the ever-widening gap between scientific discoveries and translation of those discoveries into life-changing medications. The landscape of the drug development enterprise was increasingly global, with an attending need to address cross-border issues in the regulatory, scientific, ethical, and economic arenas. The activities of the National Academies’ Forum on Drug Discovery, Development, and Translation (the Forum) in 2010 reflected this dynamic environment, focusing on five critical areas:
Keywords: Health and Medicine

Feasibility of Using Mycoherbicides for Controlling Illicit Drug Crops - National Research Council (The National Academies Press, 2011)
The control of illicit-drug trafficking and drug use is a difficult and complex process that involves a variety of prevention, control, treatment, and law enforcement strategies. Eradication strategies for controlling illicit-drug crops are used to target the beginning of the drug-supply chain by preventing or reducing crop yields. Mycoherbicides have been proposed as an eradication tool to supplement the current methods of herbicide spraying, mechanical removal, and manual destruction of illicit-drug crops. Some people regard them as preferable to chemical herbicides for controlling illicit-drug crops because of their purported specificity to only one plant species or a few closely related species. As living microorganisms, they have the potential to provide long-term control if they can persist in the environment and affect later plantings. Research on mycoherbicides against illicit-drug crops has focused on three pathogens: Fusarium oxysporum f.sp. cannabis for cannabis (Cannabis sativa), F. oxysporum f.sp. erythroxyli for coca (Erythroxylum coca and E. novogranatense), and Crivellia papaveracea or Brachycladium papaveris (formerly known as Pleospora papaveracea and Dendryphion penicillatum, respectively) for opium poppy (Papaver somniferum). Feasibility of Using Mycoherbicides for Controlling Illicit Drug Crops addresses issues about the potential use of the proposed mycoherbicides: their effectiveness in eradicating their target plants; the feasibility of their large-scale industrial manufacture and delivery; their potential spread and persistence in the environment; their pathogenicity and toxicity to nontarget organisms, including other plants, fungi, animals, and humans; their potential for mutation and resulting effects on target plants and nontarget organisms; and research and development needs. On the basis of its review, the report concludes that the available data are insufficient to determine the effectiveness of the specific fungi proposed as mycoherbicides to combat illicit-drug crops or to determine their potential effects on nontarget plants, microorganisms, animals, humans, or the environment. However, the committee offers an assessment of what can and cannot be determined at the present time regarding each of the issues raised in the statement of task.
Keywords: Agriculture

A Risk-Characterization Framework for Decision-Making at the Food and Drug Administration - National Research Council; Institute of Medicine (The National Academies Press, 2011)
With the responsibility to ensure the safety of food, drugs, and other products, the U.S. Food and Drug Administration (FDA) faces decisions that may have public-health consequences every day. Often the decisions must be made quickly and on the basis of incomplete information. FDA recognized that collecting and evaluating information on the risks posed by the regulated products in a systematic manner would aid in its decision-making process. Consequently, FDA and the Department of Health and Human Services (DHHS) asked the National Research Council (NRC) to develop a conceptual model that could evaluate products or product categories that FDA regulates and provide information on the potential health consequences associated with them.
Keywords: Food and Nutrition

Glutamate-Related Biomarkers in Drug Development for Disorders of the Nervous System: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Glutamate is the most pervasive neurotransmitter in the central nervous system (CNS). Despite this fact, no validated biological markers, or biomarkers, currently exist for measuring glutamate pathology in CNS disorders or injuries. Glutamate dysfunction has been associated with an extensive range of nervous system diseases and disorders. Problems with how the neurotransmitter glutamate functions in the brain have been linked to a wide variety of disorders, including schizophrenia, Alzheimer's, substance abuse, and traumatic brain injury. These conditions are widespread, affecting a large portion of the United States population, and remain difficult to treat.
Keywords: Health and Medicine

Building a National Framework for the Establishment of Regulatory Science for Drug Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
The Food and Drug Administration (FDA) is tasked with ensuring the safety and effectiveness of medicine. FDA's science base must be strong enough to make certain that regulatory decisions are based on the best scientific evidence. The IOM held a public workshop on February 26, 2010, to examine the state of regulatory science and to consider approaches for enhancing it.
Keywords: Health and Medicine

The New Profile of Drug-Resistant Tuberculosis in Russia: A Global and Local Perspective: Summary of a Joint Workshop by the Institute of Medicine and the Russian Academy of Medical Science - Institute of Medicine (The National Academies Press, 2011)
An estimated 2 billion people, one third of the global population, are infected with Mycobacterium tuberculosis, the bacterium that causes tuberculosis. Spread through the air, this infectious disease killed 1.7 million in 2009, and is the leading killer of people with HIV. Tuberculosis (TB) is also a disease of poverty—the vast majority of tuberculosis deaths occur in the developing world. Exacerbating the devastation caused by TB is the growing threat of drug-resistant forms of the disease in many parts of the world. Drug-resistant tuberculosis presents a number of significant challenges in terms of controlling its spread, diagnosing patients quickly and accurately, and using drugs to treat patients effectively. In Russia in recent decades, the rise of these strains of TB, resistant to standard antibiotic treatment, has been exacerbated by the occurrence of social, political, and economic upheavals. The Institute of Medicine (IOM) Forum on Drug Discovery, Development, and Translation, in conjunction with the Russian Academy of Medical Sciences held a workshop to discuss ways to fight the growing threat of drug-resistant TB. The New Profile of Drug-Resistant Tuberculosis in Russia: A Global and Local Perspective: Summary of a Joint Workshop presents information from experts on the nature of this threat and how it can be addressed by exploring various treatment and diagnostic options.
Keywords: Health and Medicine

The Emerging Threat of Drug-Resistant Tuberculosis in Southern Africa: Global and Local Challenges and Solutions: Summary of a Joint Workshop by the Institute of Medicine and the Academy of Science of South Africa - Institute of Medicine (The National Academies Press, 2011)
Tuberculosis (TB) kills approximately 4,500 people worldwide every day. While most cases of TB can be treated with antibiotics, some strains have developed drug resistance that makes their treatment more expensive, more toxic and less effective for the patient. The IOM Forum on Drug Discovery, Development, and Translation and the Academy of Science of South Africa held a workshop to discuss ways to fight the growing threat of drug-resistant TB.
Keywords: Health and Medicine

Advancing Regulatory Science for Medical Countermeasure Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Whether or not the United States has safe and effective medical countermeasures—such as vaccines, drugs, and diagnostic tools—available for use during a disaster can mean the difference between life and death for many Americans. The Food and Drug Administration (FDA) and the scientific community at large could benefit from improved scientific tools and analytic techniques to undertake the complex scientific evaluation and decision making needed to make essential medical countermeasures available. At the request of FDA, the Institute of Medicine (IOM) held a workshop to examine methods to improve the development, evaluation, approval, and regulation of medical countermeasures. During public health emergencies such as influenza or chemical, biological, radiological/nuclear (CBRN) attacks, safe and effective vaccines, treatments, and other medical countermeasures are essential to protecting national security and the well being of the public. Advancing Regulatory Science for Medical Countermeasure Development examines current medical countermeasures, and investigates the future of research and development in this area. Convened on March 29-30, 2011, this workshop identified regulatory science tools and methods that are available or under development, as well as major gaps in currently available regulatory science tools. Advancing Regulatory Science for Medical Countermeasure Development is a valuable resource for federal agencies including the Food and Drug Administration (FDA), the Department of Health and Human Services (HHS), the Department of Defense (DoD), as well as health professionals, and public and private health organizations.
Keywords: Health and Medicine; Conflict and Security Issues

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences (The National Academies Press, 2011)
Biodiversity—the genetic variety of life—is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia—in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences—and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Cooperation and Conflict," which was sponsored by the National Academy of Sciences on January 7-8, 2011, at the Academy's Arnold and Mabel Beckman Center in Irvine, California. It is the fifth in a series of colloquia under the general title "In the Light of Evolution." The current volume explores recent developments in the study of cooperation and conflict, ranging from the level of the gene to societies and symbioses. Humans can be vicious, but paradoxically we are also among nature's great cooperators. Even our great conflicts-wars-are extremely cooperative endeavors on each side. Some of this cooperation is best understood culturally, but we are also products of evolution, with bodies, brains, and behaviors molded by natural selection. How cooperation evolves has been one of the big questions in evolutionary biology, and how it pays or does not pay is a great intellectual puzzle. The puzzle of cooperation was the dominant theme of research in the early years of Darwin's research, whereas recent work has emphasized its importance and ubiquity. Far from being a rare trait shown by social insects and a few others, cooperation is both widespread taxonomically and essential to life. The depth of research on cooperation and conflict has increased greatly, most notably in the direction of small organisms. Although most of In the Light of Evolution V: Cooperation and Conflict is about the new topics that are being treated as part of social evolution, such as genes, microbes, and medicine, the old fundamental subjects still matter and remain the object of vigorous research. The first four chapters revisit some of these standard arenas, including social insects, cooperatively breeding birds, mutualisms, and how to model social evolution.
Keywords: Biology and Life Sciences

Public Health Effectiveness of the FDA 510(k) Clearance Process: Measuring Postmarket Performance and Other Select Topics: Workshop Report - Institute of Medicine (The National Academies Press, 2011)
The Food and Drug Administration (FDA) is responsible for ensuring that medical devices are safe and effective before they go on the market. Section 510(k) of the Federal Food, Drug, and Cosmetic Act requires a manufacturer of medical devices to notify FDA of its intent to market a medical device at least 90 days in advance. That window of time allows FDA to evaluate whether the device is substantially equivalent to a product already legally on the market (called a predicate), in which case the device does not need to go through the premarket approval (PMA) process.
Keywords: Health and Medicine

Establishing Precompetitive Collaborations to Stimulate Genomics-Driven Product Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Despite the many basic research discoveries in genetics, relatively few gene-based treatments, drugs, or preventative measures have been developed. One way to bridge this gap may be for industry, academia, and government to develop partnerships that share resources while distributing risk. However, intellectual property protections and other barriers can inhibit collaborative efforts. The Institute of Medicine held a workshop on July 22, 2010, to explore these issues and develop solutions.
Keywords: Health and Medicine

Generating Evidence for Genomic Diagnostic Test Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Ten years after the sequencing of the human genome, scientists have developed genetic tests that can predict a person's response to certain drugs, estimate the risk of developing Alzheimer's disease, and make other predictions based on known links between genes and diseases. However, genetic tests have yet to become a routine part of medical care, in part because there is not enough evidence to show they help improve patients' health. The Institute of Medicine (IOM) held a workshop to explore how researchers can gather better evidence more efficiently on the clinical utility of genetic tests. Generating Evidence for Genomic Diagnostic Test Development compares the evidence that is required for decisions regarding clearance, use, and reimbursement, to the evidence that is currently generated. The report also addresses innovative and efficient ways to generate high-quality evidence, as well as barriers to generating this evidence. Generating Evidence for Genomic Diagnostic Test Development contains information that will be of great value to regulators and policymakers, payers, health-care providers, researchers, funders, and evidence-based review groups.
Keywords: Health and Medicine

Direct-to-Consumer Genetic Testing: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Today, scores of companies, primarily in the United States and Europe, are offering whole genome scanning services directly to the public. The proliferation of these companies and the services they offer demonstrate a public appetite for this information and where the future of genetics may be headed; they also demonstrate the need for serious discussion about the regulatory environment, patient privacy, and other policy implications of direct-to-consumer (DTC) genetic testing.
Keywords: Health and Medicine

Medical Devices and the Public's Health: The FDA 510(k) Clearance Process at 35 Years - Institute of Medicine (The National Academies Press, 2011)
Medical devices that are deemed to have a moderate risk to patients generally cannot go on the market until they are cleared through the FDA 510(k) process. In recent years, individuals and organizations have expressed concern that the 510(k) process is neither making safe and effective devices available to patients nor promoting innovation in the medical-device industry. Several high-profile mass-media reports and consumer-protection groups have profiled recognized or potential problems with medical devices cleared through the 510(k) clearance process. The medical-device industry and some patients have asserted that the process has become too burdensome and is delaying or stalling the entry of important new medical devices to the market.
Keywords: Health and Medicine

Finding What Works in Health Care: Standards for Systematic Reviews - Institute of Medicine (The National Academies Press, 2011)
Healthcare decision makers in search of reliable information that compares health interventions increasingly turn to systematic reviews for the best summary of the evidence. Systematic reviews identify, select, assess, and synthesize the findings of similar but separate studies, and can help clarify what is known and not known about the potential benefits and harms of drugs, devices, and other healthcare services. Systematic reviews can be helpful for clinicians who want to integrate research findings into their daily practices, for patients to make well-informed choices about their own care, for professional medical societies and other organizations that develop clinical practice guidelines.
Keywords: Health and Medicine

Animal Models for Assessing Countermeasures to Bioterrorism Agents - National Research Council (The National Academies Press, 2011)
The Transformational Medical Technologies (TMT) has been a unique component of the U.S. Department of Defense (DoD) medical biodefense efforts since 2006. Its mission is to advance countermeasure research and development in support of the broader goal of the DoD to protect warfighters from emerging infectious diseases and future genetically engineered biological weapons. The TMT, using advanced science and technology approaches, focused on the development of roadspectrum countermeasures that target common host and pathogen pathways or enhance the host's immune response. Many of these pathogens are lethal or cause such debilitating diseases in humans that it is ethically inappropriate to test the efficacy of these countermeasures in human volunteers. In lieu of human participants, these products may be tested in animals and approved for human use under the provisions of the Food and Drug Administration (FDA)'s 2002 Animal Rule. The reliance on animal models for the development and licensure of medical countermeasures against biothreats is challenging for a number of reasons. The ad hoc Committee on Animal Models for Assessing Countermeasures to Bioterrorism Agents prepared a consensus report that would address the challenges stemming from developing and testing medical countermeasures against biothreat agents in animal models. Animal Models for Assessing Countermeasures to Bioterrorism Agents evaluates how well the existing TMT-employed or candidate animal models reflect the pathophysiology, clinical picture, and treatment of human disease as related to the agents of interest. The report addresses the process and/or feasibility of developing new animal models for critical biodefense research, placing emphasis on the need for a robust and expeditious validation process in terms of the FDA's Animal Rule. The report also evaluates alternatives to the use of animal models based on the premise of the Three Rs.
Keywords: Biology and Life Sciences; Food and Nutrition; Conflict and Security Issues

Sex Differences and Implications for Translational Neuroscience Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Biological differences between the sexes influence not only individual health but also public health, biomedical research, and health care. The Institute of Medicine held a workshop March 8-9, 2010, to discuss sex differences and their implications for translational neuroscience research, which bridges the gap between scientific discovery and application.
Keywords: Health and Medicine

Health Care Comes Home: The Human Factors - National Research Council (The National Academies Press, 2011)
In the United States, health care devices, technologies, and practices are rapidly moving into the home. The factors driving this migration include the costs of health care, the growing numbers of older adults, the increasing prevalence of chronic conditions and diseases and improved survival rates for people with those conditions and diseases, and a wide range of technological innovations. The health care that results varies considerably in its safety, effectiveness, and efficiency, as well as in its quality and cost. Health Care Comes Home reviews the state of current knowledge and practice about many aspects of health care in residential settings and explores the short- and long-term effects of emerging trends and technologies. By evaluating existing systems, the book identifies design problems and imbalances between technological system demands and the capabilities of users. Health Care Comes Home recommends critical steps to improve health care in the home. The book's recommendations cover the regulation of health care technologies, proper training and preparation for people who provide in-home care, and how existing housing can be modified and new accessible housing can be better designed for residential health care. The book also identifies knowledge gaps in the field and how these can be addressed through research and development initiatives. Health Care Comes Home lays the foundation for the integration of human health factors with the design and implementation of home health care devices, technologies, and practices. The book describes ways in which the Agency for Healthcare Research and Quality (AHRQ), the U.S. Food and Drug Administration (FDA), and federal housing agencies can collaborate to improve the quality of health care at home. It is also a valuable resource for residential health care providers and caregivers.
Keywords: Health and Medicine; Behavioral and Social Sciences

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2010 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This volume highlights the papers presented at the National Academy of Engineering's 2010 U.S. Frontiers of Engineering Symposium. Every year, the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and technical work. The 2010 symposium was held September 23 - 25, and hosted by IBM at the IBM Learning Center in Armonk, New York. Speakers were asked to prepare extended summaries of their presentations, which are reprinted here. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.
Keywords: Space and Aeronautics; Engineering and Technology

Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 19: Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements identifies available information and research gaps relating to the use of chemical substances by commercial drivers and is intended to provide up-to-date information to inform decision makers about the near-, mid-, and long-range planning needs for research and educational outreach programs.The report is designed to help the commercial transportation safety community and the Federal Motor Carrier Safety Administration in addressing issues involving the proliferation and availability of psychoactive chemical substances.Appendixes D and G to CTBSSP Synthesis 19 are available only in the pdf version of report.
Keywords: Transportation and Infrastructure